(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2019)
Optical Code Division Multiple Access (OCDMA) is a multiple access technique in which multiple users can access the channel simultaneously and arbitrarily. Many codes have been proposed for spectrally amplitude coded-optical code division multiple accesses (SAC-OCDMA) in order to sort out the problem of Multiple Access Interference (MAI) which is the main cause of degradation for the performance of OCDMA. In our work, code with cross-correlation c value zero has been carried out in order to overcome the problem of both Multiple Access Interference (MAI) and Phase Induced Intensity Noise (PIIN). As the value of cross-correlation c is zero, the effect of PIIN has been ignored and finds out that the performance has been degraded only because of the effect of MAI. Direct detection scheme has been used in the proposed setup and with this scheme we find out that 20 users can achieve the Bit Error Rate (BER) upto 4.21E-19, as performance is degraded by increasing the number of users. Comparison is made between different codes such as Walash Hadmard, Modified Double Weight (MDW), Dynamic Cyclic Shift (DCS) and zero cross correlation (ZCC) Random Diagonal Code (RD). Although RD has cross correlation ( c) value very small, simple code construction and less weight, but still RDC performs better.